THE INFLUENCE OF GENERATION Z CONSUMER BEHAVIOR TO USE OF THE DELIVERY FOOD SERVICE APPLICATION (SHOPEEFOOD) - Wulandari, Putri; Nurhayati, Ema; Rahman, Abdul (Institut Agama Islam Negeri Kerinci, 2024)
Purpose: This research aims to analyze the influence of Generation Z consumer behavior in using food delivery service applications, with a focus on Shopee Food. The research background reflects technological and information developments that influence Generation Z's consumption patterns, especially in the context of food delivery services. Design/Methodology/Approach: The sample used was 100 people from generation Z in Samarinda City. This research uses a quantitative approach with data collection techniques in the form of questionnaires given to 100 Generation Z respondents who use the Shopee Food application. Data analysis was carried out using statistical methods to identify the influence of consumer behavior, ease of use of the application, and Shopee Food's marketing strategy on consumer purchasing decisions. Findings: The research results show that there is a significant influence between Generation Z consumer behavior in using Shopee Food, the ease of use of the application, and marketing strategies on purchasing decisions. These factors together shape Generation Z consumers' behavior in choosing food delivery services. Research Implications: These results provide deep insight into the dynamics of Generation Z consumer behavior in the digital era, with important implications for developing marketing strategies and managing food delivery services in the future.